The advertisement call of Dendropsophus pseudomeridianus (Cruz, Caramaschi & Dias) (Anura: Hylidae) - Caram, Joana; de Luna-Dias, Cyro; Hepp, Fabio; de Carvalho-E-Silva, Sergio Potsch (Zootaxa, 2014)
The advertisement call plays a fundamental role in anuran reproduction (Duellman & Trueb 1994; Wells 2007). Some species that may be confused morphologically with each other can be distinguished by vocalization (Pombal et al. 1995). It is the case of Dendropsophus pseudomeridianus, which is phenotypically very similar to D. berthalutzae (Bokermann), D. branneri (Cochran), D. decipiens (Lutz), D. haddadi (Pombal & Bastos), D. meridianus (Lutz) and D. oliveirai (Bokermann). Herein, we present the first quantitative description of the advertisement call of D. pseudomeridianus and compare it with the advertisement call of morphologically similar species of the D. microcephalus group.